Pencil and dust (Athènes)
xv, 563 sayfa
Keywords: “The history of archaeology - particularly Classical archaeology - has long been written as a men's story, obscuring the crucial role played by women. Focusing on Greece and the wider Greek world, Pencil and Dust restores women's place in historiography by highlighting their contributions to excavations, the study of finds, and the development of methods and theory. The professionalisation of archaeology in the late nineteenth century brought about the marginalisation of women, who were relegated to the role of skilled but invisibilised - and unpaid - assistants. Yet pencil in hand, they recorded, drew, corrected, and refined archaeological knowledge. As their access to education expanded, women gradually claimed new spaces, from storerooms and museums to the field itself. Hands in the dust, these pioneers challenged gender norms while facing resistance and institutional barriers. Through biographical and thematic case studies, this volume brings their fragile, often erased legacy back into view and contributes to a more inclusive history of archaeology” --